2020
DOI: 10.15766/mep_2374-8265.10975
|View full text |Cite
|
Sign up to set email alerts
|

A Curriculum to Teach Resilience Skills to Medical Students During Clinical Training

Abstract: Introduction: Burnout in medical students is extensive and a critical issue. It is associated with increased rates of depression, suicide, and poor perception of the educational environment. Enhancing resilience, the ability to adapt well in the face of adversity, is a potential tool to mitigate burnout and improve medical student wellness. Methods: Our resilience curriculum consisted of facilitated workshops to cultivate resilience in medical students during their core clerkship rotations. This curriculum ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Bird et al report a range from 51% to 77% between two institutions in student agreement with resiliency training being a valuable use of time; similar results were reported for a voluntary program conducted for first-year residents. 8,9 The degree of variability between studies is likely due to their differing target audiences. Both this study and that by Williams et al included only firstand second-year medical students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bird et al report a range from 51% to 77% between two institutions in student agreement with resiliency training being a valuable use of time; similar results were reported for a voluntary program conducted for first-year residents. 8,9 The degree of variability between studies is likely due to their differing target audiences. Both this study and that by Williams et al included only firstand second-year medical students.…”
Section: Discussionmentioning
confidence: 99%
“…7 Bird et al's studies targeting clerkship students and interns reported lower percent agreement values. 8,9 This suggests that earlier exposure to resiliency training improves valuation, perhaps because preclinical students have more time to engage with course material and implement new habits. Unlike other elective resilience curricula reported to date, this study tracked students' use of learned skills over time.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the former, a general set of therapeutic and self-care approaches seemed to emerge, with some variation depending on the target audience. Techniques prescribed for medical students included loving-kindness meditation, Tonglen attitude/breathing practices (Bird et al, 2020) and behavioral strategies to address commonly held thought distortions (Chaukos et al, 2018); for undergraduates, mindful walks and eating, habit-breaking (Galante et al, 2018), breathing, imagining, meditating and muscle awareness relaxation (Maddi et al, 2009) strategies were taught; while nursing students participated in role-playing activities and engaged in workplace empowerment and disempowerment strategies (Pines et al, 2014), as well as mindfulness practices encouraging focused attention on observing emotions and thoughts (Van der Riet et al, 2015). Alternatively, some programs focused on enhancing personal organization skills such as a seminar-based initiative for psychology undergraduate students, which emphasized developing realistic expectations, balance, connectedness and complementary strategies of positive self-talk, stress-management and taking-action concepts (Stallman, 2010).…”
Section: Individual Strategies: Personal Skill Developmentmentioning
confidence: 99%
“…Development of students' interpersonal skills were employed in a few resilience programs, with competency training related to communication and building social connections being most common. Germane approaches covered compassionate listening training, instruction for finding meaning (Bird et al, 2020), goal clarifying in interpersonal situations and balancing interpersonal objectives skills (Lee and Mason, 2019), social interaction promotions for students studying abroad (Dresen et al, 2019) and sessions teaching students about creating meaningful connections and how decisions to maintain being a part of or withdrawing from social networks can affect behavior and health (Dolbier et al, 2010;Steinhardt and Dolbier, 2008). Another relevant approach consisted of methods targeting positive interpersonal engagement strategies.…”
Section: Interpersonal Strategies: Relational Skill Developmentmentioning
confidence: 99%
See 1 more Smart Citation